2020
DOI: 10.20944/preprints202003.0103.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MERS-CoV and SARS-CoV Infections in Animals: A Systematic Review and Meta-Analysis of Prevalence Studies

Abstract: Introduction: Coronaviruses are zoonotic viruses that include human epidemic pathogens such as the Middle East Respiratory Syndrome virus (MERS-CoV), and the Severe Acute Respiratory Syndrome virus (SARS-CoV), among others (e.g., COVID-19, the recently emerging coronavirus disease). The role of animals as potential reservoirs for such pathogens remains an unanswered question. No systematic reviews have been published on this topic to date. Methods: We performed a systematic literature review with meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
(88 reference statements)
1
2
0
Order By: Relevance
“…According to the meta-analysis, the global seroprevalence of MERS-CoV in DC is 77.4%, consistent with earlier research [ 19 ], which reported pooled seroprevalence of 73% and 83.9% by ELISA and Immunofluorescent antibody tests, respectively. The current study found that MERS-CoV prevalence and seroprevalence among the dromedaries of the Western Asia are higher than those of the rest of the world, which is supported by previous studies [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…According to the meta-analysis, the global seroprevalence of MERS-CoV in DC is 77.4%, consistent with earlier research [ 19 ], which reported pooled seroprevalence of 73% and 83.9% by ELISA and Immunofluorescent antibody tests, respectively. The current study found that MERS-CoV prevalence and seroprevalence among the dromedaries of the Western Asia are higher than those of the rest of the world, which is supported by previous studies [ 14 ].…”
Section: Discussionsupporting
confidence: 89%
“…In the beginning, we studied the three previously published systematic reviews on MERS-CoV in camels [ 14 , 19 , 20 ] and listed the reviewed articles. Then systematic data searches were conducted on Embase, PubMed, Scopus, and Web of Science on 18 April 2023 using the keywords: ((Camel OR Dromedary OR Bactrian OR Alpaca OR Llama OR Guanaco OR “Hybrid came”) AND (“Middle East respiratory syndrome” OR MERS OR “Middle East respiratory syndrome coronavirus” OR MERS-CoV)), without any timeframe of publication.…”
Section: Methodsmentioning
confidence: 99%
“…The MERS-CoV possesses the epidemic potential and continues to occur in the form of sporadic disease of humans, which remains on the Blueprint 2020 priority list of WHO, in addition to SARS-CoV, SARS-CoV-2 [142] and other emerging and life-threatening pathogens. MERS-CoV infection poses a serious health risk not only in the KSA but across the continents due to its zoonotic community acquisition and rapid nosocomial transmission [143]. The MERS-CoV is reported to be highly endemic among camels from broad areas of Africa and the Middle East, including Saudi Arabia.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%